2014
DOI: 10.1111/are.12631
|View full text |Cite
|
Sign up to set email alerts
|

Schizochytriumas a replacement for fish oil in a fishmeal free diet for jade perch,Scortum barcoo(McCulloch & Waite)

Abstract: A 10‐week trial was conducted to determine the response of juvenile jade perch Scortum barcoo on the replacement of dietary fish oil (FO) in a fishmeal free diet. Three iso‐nitrogenous, isocaloric and isolipidic diets were formulated, each containing a different primary fat source: FO, linseed oil (LO), and a mixture of Schizochytrium and LO. The substitution of FO with the mixture of Schizochytrium and LO did not cause a difference in growth. However, there was an 8% reduction in weight gain in fish fed dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 39 publications
2
26
1
1
Order By: Relevance
“…diet, which could be due to the high EPA content of the microalga itself. Similar results were also reported in Nile tilapia ( Oreochromis niloticus ) (Sarker et al, ), Jade perch ( Scortum barcoo ) (Van Hoestenberghe et al, ) and Pacific white shrimp ( Litopenaeus vannamei ) (Wang et al, ) when fed the microalga Schizochytrium sp. which was rich in DHA.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…diet, which could be due to the high EPA content of the microalga itself. Similar results were also reported in Nile tilapia ( Oreochromis niloticus ) (Sarker et al, ), Jade perch ( Scortum barcoo ) (Van Hoestenberghe et al, ) and Pacific white shrimp ( Litopenaeus vannamei ) (Wang et al, ) when fed the microalga Schizochytrium sp. which was rich in DHA.…”
Section: Discussionsupporting
confidence: 80%
“…Some microalgae rich in EPA or DHA have already been applied in aquaculture, including Crypthecodinium cohnii (Atalah et al, ; Ganuza et al, ), Phaeodactylum tricornutum (Atalah et al, ) and Schizochytrium sp. (Ganuza et al, ; Sarker et al, ; Van Hoestenberghe et al, ; Wang et al, ). However, the production cost of these organisms remains the major constraint for wide application in aquaculture (Shah et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This species is a freshwater finfish indigenous to Australia, but can be found in many countries including China, America, Malaysia and Singapore (Liu et al, ; Mok et al, ). The fish production appears to be expanding since they are hardy species with a relatively fast growth rate, good tasting flesh and high market demand (Van Hoestenberghe et al, ). Currently, there are no investigations on continuous magnetic exposure on this fish.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that the meal of the microalgae Schizochytrium can partially or totally replace fish oil in the diets for aquaculture species, such as such as salmon (Miller et al, ), sea bream (Ganuza et al, ), channel catfish (Li et al, ), jade perch (Hoestenberghe et al, ) and giant grouper (García‐Ortega et al, ). Indeed, current experiment showed that supplying 11% of Schizochytrium meal could substitute fish oil completely without significant different growth.…”
Section: Discussionmentioning
confidence: 99%
“…The microalgae is already used as feeds for rotifers and brine shrimp (Artemia) as a rich source of n‐3 and n‐6 fatty acid (Barclay & Zeller, ; Yamasaki et al, ). Schizochytrium lipid have successfully replaced fish oil in the diet for several marine species including Atlantic salmon (Miller, Nichols, & Carter, ; Sprague et al, ), channel cat fish (Li, Robinson, Tucker, Manning, & Khoo, ), giant grouper (García‐Ortega, Kissinger, & Trushenski, ) and jade perch (Hoestenberghe et al, ). In those studies, Schizochytrium sp.…”
Section: Introductionmentioning
confidence: 99%